Effectiveness of Early Mental Health Detection to Prevent Emotional Mental Disorders in Islamic Boarding School Students Experiencing Bullying: A Scoping Review - Citra Hanwaring Puri; Zahroh Shaluhiyah; Septo Pawelas Arso (Indonesian Journal of Global Health Research, 2024)
The increasing prevalence of mental health issues among students, particularly those who experience bullying, underscores the need for early detection strategies. This study examines the significance of early detection of mental health issues in santri (Islamic boarding school students) who face bullying. Purpose: The purpose of this study is to analyze the impact of bullying on the mental health of santri and to highlight the necessity for effective early detection methods. Method: A qualitative approach was employed, involving interviews and focus group discussions with santri, educators, and mental health professionals. Data were analyzed thematically to identify common patterns and insights. Result: The findings reveal a significant correlation between experiences of bullying and the emergence of mental health issues among santri. Participants reported symptoms of anxiety, depression, and low self-esteem, emphasizing the urgent need for intervention. Conclusion: The study concludes that implementing early detection mechanisms is crucial in addressing mental health issues among santri who experience bullying. Educational institutions should prioritize mental health awareness and provide necessary support systems.